Application of a Mathematical Model in Creating a Hard Alloy Tool That Combines Strength and Plasticity - Rasulov, Alisher; Tukhtayeva Malokhat; Akmal Allanazarov; Irodakhon Saidnazarova; Shokhrukh Tlovoldiyev; Kamol Khakimov; Shokhbos Botirov (International Journal of Integrated Engineering, 2025)
The article discusses the use of a mathematical model in creating a hard alloy tool that combines strength and plasticity, the development of a multi-component alloy composition using methods of planning experiments and processing test results in materials science, the preparation of a multi-component metalloceramic material from local raw materials, and their physical and mechanical properties and their role in materials science. The results of research on the use of a mathematical model in creating a hard alloy tool that combines strength and plasticity are presented. Using the steep ascent method to optimize the composition, a powder composition was determined that provided a level of stability and served as the basis for further research. An alloy with a polydisperse composition is able to embody the required properties. It is assumed that large grains of the phase provide plasticity, and small grains provide high wear resistance of the alloy.